Numeracy-Ability, Characteristics of Pupils in Solving the Minimum Competency Assessment - Lukman Hakim Muhaimin; Dadan Dasari; Yaya Sukjaya Kusumah (AKSIOMA: Jurnal Program Studi Pendidikan Matematika, 2023)
Mathematics is a subject closely related to everyday problems; the low PISA scores from all fields have made the government make breakthroughs to improve literacy and numeracy skills through the AKM. The purpose of this study was to analyze the characteristics of numeracy skills in solving AKM problems. The type of research used is qualitative with a phenomenological design. The subjects of this study used one mathematics teacher and three eighth-grade students of SMP Muhammadiyah Al Kautsar PK Kartasura Sukoharjo for the 2021/2022 academic year. Using a purposive sampling technique in taking the subject, this study used three students of class VIII as the main subject of the study. In addition to the researcher as the key instrument, the researcher also used AKM questions, interview texts, and observation texts for data acquisition. The validity used is the triangulation of sources and techniques. The inductive technique is the process of data analysis used in this research. The results of the study stated that students' numeracy skills were not perfect, indicator three on giving conclusions was not given for all subjects used. Habituation in solving AKM problems in classroom learning is needed to train students' numeracy skills.